Recycling practices of Municipal solid waste in DBKU area - Haneefa Aniza, Bt Hassan (Universiti Malaysia Sarawak (UNIMAS), 2013)
Malaysia is faced with overwhelm challenge related to solid waste management. This is due to the increase in population, economic growth, inadequate enforcement of waste legislation, lack of appropriate facilities and public attitude. One of the objectives of th· s study is to analyse public response and participation in the general recycling activities. In order to accomplish this, questionnaires consisting of 35 questions were randomly distributed to 90 respondents from selected residential areas within DBKU. Data collected were analyzed using SPSS. Results of the survey showed that the majority (61.1%) of respondents participated in recycling while the remaining (38.9010) did not. Analysis of the data showed that the main reason for the respondents to participate in recycling is their concern with the environment (98.9010). Meanwhile the main reason that hinders the respondents from participate in recycling is inadequate or poor recycling campaign, no monetary benefit as well as minimum recycling facilities provided by the municipal.